SAKRAMEN REKONSILIASI SEBAGAI PEMBAHARUAN HIDUP BERIMAN BAGI UMAT DI STASI SANTO PETRUS MAJUNDRE PAROKI SANTO PAULUS BUNTOK - Yustinus Hendro; Romanus Romas; Silvester Adinuhgra (Sepakat : Jurnal Pastoral Kateketik, 2021)
The study aims to describe the sacrament of reconciliation as the renewal of the life of faith for the people in the Stasi of St. Peter Majundre Parish of St. Paul Buntok. Through this study, people are expected to realize and live the sacrament of reconciliation as a renewal of life in the life of the faithful. The type of research used is qualitative research with data collection techniques using interviews, and documentation. The data processed by 10 informants divided into two parts, namely eight people consisting of people in the Stasi St. Peter Majundre, one person working as the head of the parish in Stasi St. Peter Majundre and also one person working as Parish Priest in St. Paul Buntok Parish. Data analysis techniques use Miles and Huberman's theory which is divided into three stages, namely data reduction, data presentation, and inference.